2016
DOI: 10.1111/1541-4337.12242
|View full text |Cite
|
Sign up to set email alerts
|

The Use and Performance of Household Refrigerators: A Review

Abstract: The domestic refrigerator is now a common household device with very few households in the developed world not possessing 1, or more, for the storage of chilled foods. Domestic storage is the last, and in many respects the most important, link in the food chill chain. Inadequate domestic refrigeration or cooling is frequently cited as a factor in incidents of food poisoning. The authors reviewed the temperature performance of refrigerators in 2008. This new review builds on that review, covering studies that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(67 citation statements)
references
References 111 publications
(129 reference statements)
5
60
1
1
Order By: Relevance
“…Although the lowest temperature was kept at 4 • C, the temperature in the refrigerator was sometimes higher than 7 • C during the experiment, as lots of refrigerators are in reality running at higher temperature than set [35]. In our experiment, the temperature fluctuation did happen (Figure 4) when the refrigerator was opened for taking out sample eggs and fluctuated with the cooling system running.…”
Section: Time-temperature Fluctuationmentioning
confidence: 75%
“…Although the lowest temperature was kept at 4 • C, the temperature in the refrigerator was sometimes higher than 7 • C during the experiment, as lots of refrigerators are in reality running at higher temperature than set [35]. In our experiment, the temperature fluctuation did happen (Figure 4) when the refrigerator was opened for taking out sample eggs and fluctuated with the cooling system running.…”
Section: Time-temperature Fluctuationmentioning
confidence: 75%
“…They concluded that many refrigerators were running at higher than recommended temperatures. Since 2008, there have been several papers published on temperatures in domestic refrigerators (James et al (2017), Roccato et al (2017), Hassan et al (2015), Evans et al (2014), Geppert (2011), Landfeld et al (2011) and WRAP (2009). These generally concur with the results from the James et al (2008) review.…”
Section: Cold Appliance Operationmentioning
confidence: 99%
“…The frequency and for how long a door is opened are known, generally, to affect the cooling performance of refrigerators, especially for household refrigerators. Several authors have noted a heat gain caused by door openings and, consequently, an increase in a refrigerator's energy usage [29]. The door size here us not significantly related to the size of the warehouse (in contrast to the household refrigerator, where the door size represents a significant portion of the overall surface).…”
mentioning
confidence: 57%